(untitled) (Global Journal of Human-Social Science, 2012)
In the age of globalization it was argued that major cities in the region should be positioned in the global city system in order for these cities and their immediate regions are effectively developed At the same time the emergence of new global economic and informational societies has created a new form of spatial development the global cities Such status was achieved only when a city and its region becomes a major center of international finance transnational corporate headquarters related high-level and specialized services information processing and advanced telecommunications a city with an international command and control functions The aspiration for Kuala Lumpur City-Region KLCR is to drive rapid growth parallel with upgrading the city s liveability according to the Economic Transformation Programme ETP s A Roadmap for Malaysia